Development of Heyzine-assisted handout on human respiratory system material in the eighth grades of junior high school - Tiara Marantika Natalia; Eko Sri Wahyuni; T. Titin (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
E-handout is one form of teaching material that can be used by teachers and students in the learning process. This research aims to develop teaching materials in the form of e-handouts using Heyzine to determine the feasibility and practicality of e-handouts on human respiratory system material in the 8th grade of junior high school. The research method used is Research and Development with the Analysis, Design, Develop, Implement, and Evaluate (ADDIE) model. However, this study only carried to the implement stage. The data sources of this study were 18 9th-grade students from SMP Negeri 6 Menyuke; 3 science teachers from SMP Negeri 29 Pontianak, SMP Negeri 5 Menyuke, and SMP Negeri 6 Menyuke; and 2 lecturers of Biology Education FKIP UNTAN. The results of validation of the e-handout were obtained, namely 0.95, which was categorized as valid. The interrater reliability results using the Intraclass Correlation Coefficient (ICC) obtained results of 0.430, which falls into the fair to good category. The e-handout practicality test results obtained 83.53%, which falls into the very practical category. It can be concluded that the development of a Heyzine-based e-handout on human respiratory system material for class VIII students is considered valid and very practical as teaching material. However, this study has several limitations. Research was only carried out up to the implementation stage in the ADDIE model, so the effectiveness of e-handouts in increasing student understanding cannot yet be measured thoroughly.